Color changes of nanofiller composite resin after glycerin application immersed in turmeric extract - Sukaton; Sampoerno, Galih; Laksmi, Widyajeng Ayu; Santiaji, Daradhasih Bestari (Conservative Dentistry Journal, 2023)
Background: Nanofiller composite resin has good mechanical strength also used for restoration that require aesthetics. However, resin composites can experience discoloration resulting in extrinsic or intrinsic factors. To produce perfect polymerization, glycerin can be used as an air-inhibition coating to prevent the formation of Oxygen-Inhibited Layer resulting in a more stable over discoloration. Purpose: To knowing the color change due to the application of glycerin on nanofiller composite resin immersed in turmeric extract solution. Method: It is a laboratory experimental study with a Pre-Test-Post-Test Control Group Design using 28 samples of 3M ESPE Filtek 350XT nanofiller composite resin divided into 4 groups, namely the group with glycerin application and without glycerin application which were soaked in turmeric extract with and saline for 4 days. The color changes were measured using a CHNSpec CS-10 colorimeter before and after immersion. Results: Nanofiller composite resin with turmeric extract immersion without glycerin application had an average discoloration of 90.97 + 23.26 while with glycerin application it had a lower average of 84.37 + 9.24. On the results of the independent sample t-test with a significant level of 5%, it has a value of p = 0.506 > 0.05. Conclusion: Composite resin with glycerin application experienced less color change than composite resin without glycerin application in turmeric extract immersion, but statistically not significant.